(untitled) (Fiep Bulletin - online, 2014)
INTRODUCTION: The predict of heart risk and of occlusive arterial diseases outlying (DAOP) measured by techniques of easy application have been studied thoroughly in the extent of the sciences of the health. OBJECTIVE: To analyze the risk of Occlusive Arterial Disease of Inferior Limbs (DAOMI) for levels of Index Brachial Ankle (ITB), in the elderly. MATERIAL AND METHODS: Elapses of a study descriptive, transverse, sample 31 voluntary individuals, with average of 73,29 5,75dp year old age, submitted to the anamnesis tests, systolic blood pressure (PAS) of the arms right (BD) and left (BE) and of the legs right (PD) and left (PE), disposing in practice the ITB, with cut point of Serious for values of <0,40 and> 1,40, 0,41 to 0,70 Moderate 0,71 to 0,90 Light,> 0,90 Normal. The analytical plan used program SPSS 13.0, for statistics of Average, Standard Deviation, Maximum and Minimum, "r" of Pearson. Level of trust 5%. RESULTS: The found values were: ITB-RIGHT 0,970,06, ITB-ESQUERDO 0,990,07, PASBD 133,5423,74, PASBE 133,5423,31, PASPD 132,9024,79, PASPE 134,1923,20. O "r" de Pearson find correlations among Pains in the Legs When Walks (DPQC) and Classification Left ITB (r=0,964) Place of the Pain (LD) and Practice Physical Activity (PAF) (r = 0,935), PAF and PASBE (r=0,750), Arterial Hypertension (HA) and Age (ID) (r=0,970), PASBD and LD (r=0,8330), PASPD and Classification Left ITB (r=0,904), PASPE and ID (r=0,955), ITB Direito and Classification Left ITB (= 0,793), Left ITB and PASPD (r=0,864). CONCLUSION: The average of the values of PAS is classified as hight normal presenting a larger risk for the male individuals; the medium values of ITB don’t expose the studied population DAOMI and cardiovascular risk, this way it was verified in this sample that the age is a factor of risk in the appearance of DAOMI and of the arterial hypertension.